KLAUSA VERBAL DALAM CERPEN UCHIBBUKA KAL-MĀ´I KARYA LĪNA KĪLANĪ: (ANALISIS SINTAKSIS) - Bunga Suryani, Afnan Arummi (CMES (Center of Middle Eastern Studies), 2016)
This research studies about verbal clause or jumlahfi’liyah. Clause is a series or combination of words comprises of subject and predicate which potentially becomes a sentence. The analysis is done based on the structure and the types of clause within the data. Data collection is done by scruntinizing (simak) and notetaking (cakap) method. Apportion method is used as the data analysis by applicating direct elemenets-dividing as the ground technique and divestation, alteration, and mark reading technique as the following techniques. Afterward, the result of the analysis is presented informally. This study results severalconclusions. First, there are 87 verbal clauses found within Uchibbuka kal-Ma´i short story.Second, structurally, there are 24 full clauses and 63 partial clauses found in the short story. Third, based on the types of clauses in Arabic, there are 26 functionated clauses within sentence; they are: 20 al jumlatu al- waqi’atukhabaran, 3 al-jumlatu al-waqi’atu chalan, and 3 al-jumlatu al-waqi’atushifatan. However, there are 61 data included as unfunctionated clause within sentence; they are: 11 al-jumlatu al-ibtidaiyyatu, 12 al-jumlatu al-waqi’atushillati al-maushuli, 1 aljumlatu al-waqi’atu jawab li’s-syarthighairujazim, 1 al-jumlatua’t-tafsiriyatu, 36 a’t-tabi’atu li jumlatin.